2010
DOI: 10.1111/j.1753-6405.2010.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the determinants of food insecurity in New Zealand and does this differ for males and females?

Abstract: Aims: Food insecurity is a lack of assured access to sufficient nutritious food. We aimed to investigate the demographic and socio‐economic determinants of food insecurity in New Zealand and whether these determinants vary between males and females. Methods: We used data from the longitudinal Survey of Families, Income and Employment (SoFIE) (n=18,950). Respondents were classified as food insecure if, in the past 12 months, they had to use special food grants or food banks, been forced to buy cheaper food to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
76
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 18 publications
11
76
1
5
Order By: Relevance
“…Food insecurity among New Zealand households with children is even greater, with 20% reporting that they could not always afford to 'eat properly' (Ministry of Health 2003) in 2002 Food insecurity is an indicator of socio-economic distress and hardship ), but not all families experiencing economic hardship are food insecure, and vice versa. In New Zealand, more than 10% of adults who are employed (14%), have achieved university-level degrees (11%), and own their own homes (11%) experience food insecurity (Carter et al 2010). Food insecurity is also unique in that it poses a distinct stress on families and affects the quality and quantity of foods that families consume (Drewnowski and Specter 2004;Utter et al 2012).…”
mentioning
confidence: 99%
“…Food insecurity among New Zealand households with children is even greater, with 20% reporting that they could not always afford to 'eat properly' (Ministry of Health 2003) in 2002 Food insecurity is an indicator of socio-economic distress and hardship ), but not all families experiencing economic hardship are food insecure, and vice versa. In New Zealand, more than 10% of adults who are employed (14%), have achieved university-level degrees (11%), and own their own homes (11%) experience food insecurity (Carter et al 2010). Food insecurity is also unique in that it poses a distinct stress on families and affects the quality and quantity of foods that families consume (Drewnowski and Specter 2004;Utter et al 2012).…”
mentioning
confidence: 99%
“…Food insecurity is associated with poorer nutritional outcomes (2)(3)(4)(5) , and in New Zealand (NZ) and other developed countries it is more likely to be experienced by low socio-economic groups. In NZ there is emphasis on the need to consider methods of improving food security (6,7) . Changes to the tax levels for some foods (e.g.…”
mentioning
confidence: 99%
“…The positive relationship between real per capita GDP and food supply suffi ciency suggests that the substitution effect associated with rising real per capita GDP is outweighed by the larger production scale effect associated with real per capita GDP. The positive link between real per capita GDP and food availability (food security) is shown by Carter et al (2010), Herath et al (2014) and Tadese et al (2014). The impact of domestic prices on food availability is negative.…”
Section: Determinants Of Physical Availability Of Food: Aggregate Anamentioning
confidence: 98%
“…The relative importance of demand-side and supply-side factors have been argued by Feleke et al (2005) who found that the latter are more powerful determinants of food security than the former. Counter arguments in favour of demandside variables have also been documented (Kargbo, 2000;Carter et al, 2010;Herath et al, 2014;Tadese et al, 2014).…”
Section: Determinants Of Food Securitymentioning
confidence: 99%
See 1 more Smart Citation